Mapping dynamic branch displacements: A versatile method to quantify spatiotemporal neurite dynamics - Hiramoto, Masaki; Cline, Hollis T. (Frontiers in Neural Circuits, 2011)
Abstract Quantification of the movement of axons and dendrites is essential to study circuit formation. Several methods have been developed to quantify the movement of neurites in simplified systems, however these quantification methods are specialized for a limited type of predicted movements in the particular assay systems. The movement of neurites in vivo includes many unexpected rearrangements. Establishment of a method that can detect and quantify a variety of patterning events will reveal novel phenomena in circuit formation and make it possible to conduct deeper investigation of the molecular and cellular bases of these events. Here we present a versatile method that represents a quantitative analysis of the integrated movement of neurites on a spatial map. We show that the method is useful to analyze several types of neurite behaviors, such as changes in the directionality of neurite movements, fasciculation of axons or changes in territories of dendritic fields.